Experimental study on forced convective heat transfer of supercritical carbon dioxide in a horizontal circular tube under high heat flux and low mass flux conditions. (March 2019) - Wang, Junhui; Guo, Pengcheng; Yan, Jianguo; Zhu, Fengling; Luo, Xingqi
This study focuses on the convective heat transfer characteristics of supercritical carbon dioxide flowing in a horizontal circular tube under high heat flux and low mass flux conditions. The influences of thermophysical property, buoyancy effect, and thermal acceleration on the heat transfer characteristics are discussed. The parameters are as follows: system pressure is 7.6–8.4 MPa, mass flux is 400–500 kg/m 2  s, heat flux is 30–200 kW/m 2, fluid temperature is 20°C −62°C, and Reynolds number is 1.23 × 10 4 to 4.3 × 10 4 . The wall temperature and heat transfer coefficient of supercritical carbon dioxide are obtained. The results show that, under the condition of high heat flux and low mass flux, heat transfer deterioration would happen, in which thermophysical property and buoyancy effect are the main factors. When the pressure is 7.6 MPa, the buoyancy factor is greater than 10 −3 in the whole heat transfer area, and the buoyancy effect cannot be ignored, while the thermal acceleration factor is 9.5 × 10 −8 to 4 × 10 −6 and the effect of thermal acceleration can be negligible. The experimental data are compared with the predictions using seven empirical correlations, in which the Liao–Zhao correlation shows the best performance.